Aspirational paternity and the female gaze on Korean reality–variety TV. (March 2020) - Jung, Grace
Korean public broadcasters are reconstructing local fatherhood through two popular reality–variety shows Dad! Where Are We Going? (MBC, 2013–2015) and The Return of Superman (KBS, 2013–) wherein celebrity dads look after their children for 2 days without the help of their wives. The shows exemplify Korean 'telemodernity', which describes Asia's aspirational modernity channeled through lifestyle television programs. These examples of Korean telemodernity strive toward a Western exemplary of fatherhood by breaking from the earlier generation's paternity, described through an internalized orientalist self-perception as emotionally unavailable. The paternal masculinity that these shows idealize is visible through the mise-en-scene that frames scenarios around the female (mother's) gaze of approval or disapproval. In a nation panicked by low childbirths, these shows are biopolitical in their design to encourage heteronormative coupling and reproduction among women more so than promote household egalitarianism.